THREE-DIMENSIONAL QUANTITATIVE STRUCTURE–ACTIVITY RELATIONSHIPS MODELING STUDIES OF PHYTOCHEMICALS FROM BRASSICACEAE AS POTENT INHIBITORS AGAINST TUMOR INFLAMMATION - J, RenukaDevi; G, Nandhinidevi; M, Bavanilatha; Bharathy T, Kavitha; Banu M, Jameela; S, Kanimozhi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study was to develop a three-dimensional quantitative structure–activity relationships (3D-QSARs) model for studying theinteraction of different phytochemicals with nuclear factor kappa B (NF-ĸB) inducing kinase, a major regulator in tumor inflammation. Methods: Different phytochemicals (ligands) from Brassicaceae were selected and tested for Lipinski's rule of five and further analyzed using interaction studies (docking) to identify the binding site in the target protein. Ligands with best fit were made to pass through ADMET filter, and the nontoxic ligands were selected based on the pIC50 values. Results: The 3D-QSARs of the ligands were designed using comparative molecular field analysis, and glucoraphanin was found to be stable and fit after subjecting for molecular dynamics simulation with annealing studies. Conclusion: Thus, the model may be prospectively used in drug design to find possible inhibitors of NF-ĸB, which plays a key prominent role in cancer inflammation. Keywords: Three-dimensional quantitative structure–activity relationships, Brassica oleracea, Simulation, Annealing, Nuclear factor kappa B kinase.